Bioinformatic prediction, annotation and experimental validation of conserved microRNAs in Lactuca sativa Linn - Shehnaz Shair Qambrani; Muhammad Naeem Shahwani; Iftekhar Ahmed Baloch; Shahjahan Shabir Ahmed Rana; Asma Abro (Scientific Reports)
Abstract MicroRNAs (miRNAs) are non-coding RNAs that play crucial role in post-transcriptional gene regulation, with lengths ranging from 18 to 26 nucleotides (nt). These endogenously expressed molecules exhibit significant evolutionary conservation, a feature vital for identifying new conserved miRNAs across various plant and animal species. Lettuce (Lactuca sativa Linn.), a member of the Asteraceae family, stands out as a leafy vegetable with exceptional nutritional value. Given its significance, this study aimed to discover and describe new conserved miRNAs in lettuce. The investigation employed computational techniques to explore the lettuce genome leading to the identification of 27 conserved miRNAs from 27 families. Notably, three clusters of precursor miRNAs (pre-miRNAs), including lsa-MIR165, lsa-MIR168, and lsa-MIR3630, were also identified. To validate the computational predictions, seven randomly selected miRNAs were experimentally validated using RT-PCR. Additionally, the study delved into the protein targets of the identified miRNAs, resulting in the identification of 74 protein targets associated with 97 Gene Ontology (GO) terms and significant biological processes. The computational analysis of targets also shed light on their potential roles in post-transcriptional regulation. The presence of three precursor miRNA clusters suggested coordinated regulatory functions. The identification of conserved miRNAs and their associated protein targets opens avenues for understanding the molecular mechanisms underlying regulatory processes in this economically significant leafy vegetable and the knowledge gained from this research lays the groundwork for potential applications in modulating miRNAs to control desired features in lettuce, thereby contributing to the improvement of this essential crop.